2018
DOI: 10.2147/ijn.s165005
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of chitin-amphipathic anion/quaternary ammonium salt ecofriendly dressing and its effect on wound healing in mice

Abstract: ObjectiveThis study aimed to prepare an eco-friendly dressing using a chitin-derived membrane with amphipathic anion/quaternary ammonium salt designed for antibacterial purposes.MethodsFour dressings were prepared and group A was chitin, group B was chitin + amphiphilic ion, group C was chitin + quaternary ammonium salt, group D was chitin + amphiphilic ion + quaternary ammonium salt.ResultsIn the group D material, precipitation of adherent composite ions was observed. The contact angle test showed that the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Most papers are dedicated to chitosan or ionically cross-linked chitin microspheres [52]. In one case, a chitin–amphipathic anion/quaternary ammonium salt dressing was prepared [53]. In our study, however, we utilized a recognized antibacterial compound—decamethoxine.…”
Section: Discussionmentioning
confidence: 99%
“…Most papers are dedicated to chitosan or ionically cross-linked chitin microspheres [52]. In one case, a chitin–amphipathic anion/quaternary ammonium salt dressing was prepared [53]. In our study, however, we utilized a recognized antibacterial compound—decamethoxine.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that this dressing had good antipollution and antibacterial activities which promoted wound healing. [ 71 ] Other typical cases of chitin used in antibacterial wound repair are presented in Table 1 .…”
Section: Applications Of Edible Materials In Skin Wound Healingmentioning
confidence: 99%
“…Furthermore, Pseudomonas aeruginosa -infected wounds in db/db diabetic mice were diminished by cleaning with cleansing agent hypochlorous acid and covering with silver nanoparticle/chitin in the form of nanofiber sheet [ 225 ]. Chitin-amphiphilic ion/quaternary ammonium salt having antibacterial and antipollution effects was also used for wound healing [ 226 ]. Chitin-lignin gels, as an extracellular matrix-like scaffold, were applied as wound dressing material that had a property of sustainable drug release especially antibiotics [ 227 ].…”
Section: Potential Applications Of Chitin and Chitosan Oligosacchamentioning
confidence: 99%